Pengaruh Kemandirian Belajar Serta Ketersediaan Sarana Dan Prasarana Pendidikan Terhadap Hasil Belajar Mahasiswa Di Perguruan Tinggi - Putri Calista Rohandiana; Christian Wiradendi Wolor (Education : Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study was made to determine the influence of learning independence and the availability of educational facilities and infrastructure on student learning outcomes in universities. As for this study, a type of research with quantitative research methods along with descriptive analysis was used. All data were collected using a questionnaire measured using a Likert scale from value one to value five involving 100 random students as a sample in the study. Then, the data analysis technique used in this study is a linear regression technique, which consists of validity, reliability, normality, linearity, autocorrelation, multicollinearity, heteroscedasticity, f-test, t-test and determination coefficient test using the SmartPLS 4 software application. The results of this study show that there is a positive and significant influence between the independence of learning on learning outcomes, there is a positive and significant influence between the availability of educational facilities on learning outcomes, there is a positive and significant influence between the availability of educational infrastructure on learning outcomes, there is a positive and significant influence between learning independence and the availability of educational facilities and infrastructure together on learning outcomes.